An Analysis of the Functions and Impacts of Debt Payment Moratoriums (PKPU) from the Perspective of Justice - Agatha Gabriella Setyono; Suhartati Suhartati (CV. Publikasi Indonesia, 2026)
Postponement of Debt Payment Obligations (PKPU) is a legal mechanism that provides an opportunity for debtors who are unable to pay debts to get more time to carry out debt restructuring and avoid bankruptcy. This study aims to analyze the function and impact of the Suspension of Debt Payment Obligations (PKPU) on debtors and creditors and assess its conformity with the principles of justice. The research method used was normative juridical with a legislative approach and a conceptual approach. The results of the study show that PKPU has its main function as a means of debt restructuring to provide opportunities for debtors to avoid bankruptcy while providing legal certainty for creditors in fulfilling their rights. In practice, PKPU can have various impacts, both positive and negative. Procedurally, the PKPU mechanism has basically reflected the principles of justice, but it still leaves loopholes that allow violations to occur. Therefore, it is necessary to strengthen regulations and strict supervision so that the implementation of PKPU can better reflect the principles of legal justice as a whole.